Implikasi peraturan kerangka kerja manajemen keuangan publik pada penyediaan layanan : refleksi majelis distrik negara ghana - Fahri Juarsa Muhammad; Herijanto Bekti; Yogi Suprayogi Sugandi (Publisia: Jurnal Ilmu Administrasi Publik, 2020)
Public Financial Management a set of laws, rules and standards is an important part of regulating the systems and processes used by each sovereign state and local government, in order to mobilize revenue, allocate public funds, conduct public spending, and budget audits. The purpose of public financial management itself is to increase efficiency and transparency in the use of public resources and eliminate the inefficiency of public resources. The regulatory framework for Public Financial Management is able to carry out analytical and critical practices in helping to facilitate services efficiently and effectively. This article uses a qualitative method with a descriptive approach as to describe or analyze a research result but is not used to make a broader conclusion. Analysis and Discussion The Government of Ghana is aware that there are regulations governing the budgeting, although some of them do not understand and study these documents comprehensively. The regulatory framework governing fund management influences service delivery. In conclusion, the regulatory framework explains how public budgets are used to provide better services. The regulation is designed with the aim of helping to reduce budget waste and prevent corruption. DOI: 10.26905/pjiap.v5i1.3860